Entrepreneurship Centres - Paul Jones (Palgrave MacMillan, 2017)
Focusing on the role entrepreneurship centres can play within the UK and other countries; this edited volume explores the effective construction of viable and sustainable entrepreneurship centres. It questions how these Higher Education Centres contribute to enterprise and entrepreneurship curriculum enhancement, research, and support to entrepreneurs. Entrepreneurship Centres responds to the renewed focus on Higher Education Institutions to play a meaningful role in socio-economic development and the need for such centres to act as an equal component to the traditional roles of teaching and research within universities. With case studies from the UK, Africa, Europe, and Canada, this collection contributes to the debate on whether entrepreneurship centres can and should play an important role in entrepreneurship activities within HEIs.